(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
Nowadays, the development of the working world requires education to bestow the graduates with numbers ofrequired abilities and one of which is working skills. Forming students’working skills requires a continuous process, including career development activities as guidance and consultation in school.This study concerns the absence of career development media for students. The purpose is to develop a Pocket Book for Artistic Working Environment as the career development media for students. This Research and Development study employed the following steps: (1) potentials and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, and (6) product testing. The data were obtained from experts’ validation and product testing to be analyzed qualitatively. The findings from the validation of media, language, guidance/counseling expert, and product testing by the guidance/counseling teacher revealed that the pocketbook could be implemented as a career development media in an Artistic Working Environment for the students, especially in an artistic-related work environment.